ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KEMAUAN MEMBAYAR PELAYANAN RAWAT JALAN PUSKESMAS DI KABUPATEN BANYUMAS - Arif Kurniawan; Arih Diyaning Intiasari (Kesmas Indonesia, 2011)
ABSTRACT The cost of outpatient care unit of the organization's first level health centers in Banyumas higher than the tariffs imposed at this time. The result is still needed government subsidies to cover operational costs shortage of health service delivery level of the first outpatient clinic. The results Kurniawan and Intiasari (2010) shows the average willingness to pay the community is still low. This prompted research to find out what factors affecting willingness to pay outpatient services at Puskesmas in Banyumas district. This study was survey research with explanatory research. The approach in this study using cross-sectional. The study population was people who visit the Puskesmas in 2009. The sample of this study some 105 people, with a minimum sample size formula.The result of this research shows ATP has a diverse community with an average of Rp. 21908.63 ATP and WTP are varied with an average WTP of Rp. 3770.00. There is a relationship of age, ATP, and food expenditure by the public willingness to pay tariffs outpatient clinic services. There is no relationship between level of education, gender, occupation, non-food expenditure by the public willingness to pay tariffs outpatient clinic services. There are the influence of age together and ATP on the willingness of society to pay tariffs at Puskesmas. As suggestion for Puskesmas can prioritize community with the productive age group and a high ATP as outpatient service utilization. Puskesmas should consider the community that has a low ATP but has a higher WTP in order to take advantage of outpatient clinic services. Keywords: Kemauan membayar , Puskesmas Kesmasindo. Volume 4(2), Juli 2011, hlm. 105-118